Modulation of the N170 with Classical Conditioning: The Use of Emotional Imagery and Acoustic Startle in Healthy and Depressed Participants - Camfield, David A.; Mills, Jessica; Kornfeld, Emma J.; Croft, Rodney J. (Frontiers in Human Neuroscience, 2016)
Recent studies have suggested that classical conditioning may be capable of modulating early sensory processing in the human brain, and that there may be differences in the magnitude of the conditioned changes for individuals with major depressive disorder. The effect of conditioning on the N170 ERP was investigated using neutral faces as conditioned stimuli (CS+) and emotional imagery and acoustic startle as unconditioned stimuli (UCS). In the first experiment EEG was recorded from 24 undergraduate students (M = 21.07 years, SD = 3.38 years) under the following conditions: i) CS+ / aversive imagery, ii) CS+ / aversive imagery and acoustic startle, iii) CS+ / acoustic startle, and iv) CS+ / pleasant imagery. The amplitude of the N170 was enhanced following conditioning with aversive imagery as well as acoustic startle. In the second experiment 26 healthy control participants were tested (17 females and 9 males, age M = 25.97 years, SD = 9.42) together with 18 depressed participants (13 females and 5 males, age M = 23.26 years, SD = 4.01) and three conditions were used: CS+/aversive imagery, CS+/pleasant imagery and CS- . N170 amplitude at P7 was increased for the CS+/aversive condition in comparison to CS- in the conditioning blocks versus baseline. No differences between depressed and healthy participants were found. Across both experiments, evaluative conditioning was absent. It was concluded that aversive UCS are capable of modulating early sensory processing of faces, although further research is also warranted in regards to positive UCS.